A comparative, randomized, prospective, two‐center clinical study to evaluate the clinical and esthetic outcomes of two different bone grafting techniques in early implant placement. Issue 3 (15th November 2018) - Mau, Jimmy LianPing; Grodin, Evan; Lin, Jung‐Jen; Chen, Mark Chun‐Jung; Ho, Chung‐Han; Cochran, David
Abstract: Background: Early implant placement combined with simultaneous contour augmentation was able to rebuild stable facial hard‐tissue and soft‐tissue contours that were esthetically pleasing. The purpose of this study was to evaluate the clinical esthetic outcome, when two different bone grafting materials were used. Methods: Forty‐eight patients were randomly assigned into two groups. In the control group, autogenous bone was used to cover the exposed implant surface then a layer of deproteinized bovine bone mineral (DBBM) was added. This graft combination was then combined with a collagen membrane. In the test group, the exposed implant surface was covered with a layer of freeze‐dried bone allograft (FDBA) in combination with the collagen membrane. Modified plaque index (mPI), modified sulcular bleeding index (mSBI), probing depth (PD), keratinized mucosa (KM), implant crown length (IC), distance from the implant shoulder radiographic bone‐to‐implant contact (DIB), pink esthetic score (PES), and white esthetic score (WES) were measured at 12‐months post implant loading. Results: All 48 implants were clinically successful, and no significant differences were observed in mPI, mSBI, PD, KM, IC, DIB, PES, and WES at 1‐year implant loading. The mean mucosal recessions of test and control group were unchanged, 0 and –0.02 mm, respectively. The mean DIB were –0.32 and –0.21 mm in test and control implants, respectively. The mean totals of PES/WES were 15.29 and 15.33 for the test and control groups, respectively, with no significant difference between groups. Conclusion: This study demonstrated that autogenous bone plus DBBM and FDBA each combined with a collagen membrane both resulted in stable clinical and esthetic outcomes in early implant placement with contour augmentation after 1 year.